Antigenic and molecular characterization of rabies virus in Argentina - Cisterna, Daniel (2005)
Fil: Cisterna, Daniel. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Servicio de Neurovirus; Argentina.